Effect of NPK Fertilizers on Plant Growth Gmelina (Gmelina arborea Roxb.) In Media Land Former Gold Mine (Tailings) - Basuki Wasis; Nuri Fathia (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2011)
Mining activities can have negative impact on the environment if the waste they produce is not processed properly. Negative impacts include disruption of natural ecosystems such as changes in soil structure resulting morphology and physical conditions, chemical and biological soil becomes worse. Tailings are mineral composite weight from mining activities, has a sandy texture. Composites is a waste of mining and no economic value. Given these tailings will disrupt the ecosystem of the environment so that the quality and productivity of the environment will decrease. Revegetation activities (afforestation) is one of the vegetative techniques that can be applied in an effort to rehabilitate the damaged land. Crop planting Gmelina arborea Roxb. tailings in the media with the addition of NPK fertilizer is expected to improve the physical properties, chemical and biological soil tailings as a medium of plant growth in land revegetation efforts.